2001
DOI: 10.1001/archsurg.136.8.892
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller Myotomy Improves Esophageal Emptying and the Symptoms of Achalasia

Abstract: Hypothesis: Laparoscopic Heller esophageal myotomy improves esophageal clearance and symptoms of achalasia in the early and late postoperative periods. Design: We followed up 98 consecutive patients attending a referral center between February 1, 1994, and July 1, 2000, who underwent laparoscopic myotomy. Operative time, complications, and length of stay were recorded. Postoperative outcomes were assessed using Van Trappen symptom scores (1 indicates no symptoms; 2, symptoms occurring less than once a week; 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 16 publications
4
25
1
2
Order By: Relevance
“…Oesophageal perforation was the most common complication of this procedure which was encountered in most of the other studies like Yamamura MS et al, Peclivanides G et al, Finely RJ et al, Decker G et al and Chuah S et al 9,11,14,14,18 In all the above studies including present study oesophageal perforation was sutured intraoperatively without any major complication.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Oesophageal perforation was the most common complication of this procedure which was encountered in most of the other studies like Yamamura MS et al, Peclivanides G et al, Finely RJ et al, Decker G et al and Chuah S et al 9,11,14,14,18 In all the above studies including present study oesophageal perforation was sutured intraoperatively without any major complication.…”
supporting
confidence: 53%
“…Finley RJ et al, showed only 2 patients (3.50%) developed new heart burn and reflux oesophagitis postsurgery on regular follow up 14 Sharp KW et al, showed that only mild degree of relax oesophagitis developed in 14 patients out of 100 patients who underwent laparoscopic Heller's myotomy. 12 Zaninotto G et al, showed recurrence of dysphasia in 10% of patients with mean follow up of 8 months.…”
mentioning
confidence: 99%
“…63 This technique is associated with greater decreases in dysphagia, shorter hospital stays, lower risks of post-operative GER, improved oesophageal emptying and low complications. 38,[64][65][66] Large series and reviews have demonstrated 90% overall symptomatic improvement following the surgery 18,38 with >80% remaining dysphagia free at 5 years.…”
Section: Surgerymentioning
confidence: 99%
“…Studies including large number of patients have shown that an extramucosal myotomy of the esophagus and cardia combined with an anterior fundoplication can be performed safely and effectively through laparoscopy, with clinical and functional results similar to that obtained with the open transabdominal approach and relief of dysphagia in more than 90% of patients [17][18][19][20][21][22] . Although previous endoscopic treatments, such as balloon dilatation or intrasphincteric botulinum toxin injection, may cause submucosal scarring at the esophagogastric junction resulting in a more difficult surgical procedure and an increased operative morbility, no statistically significant differences as far as concern the clinical outcome have been reported [15] .…”
Section: Minimally Invasive Surgery For Achalasiamentioning
confidence: 99%